A Comparative study between the spectra of prostate Cancer and healthy men using FTIR- ATR technique - Adhab, Hiba Ghmeedh; alshebly, Shaymaa Awad Kadhim (International Journal of Psychosocial Rehabilitation, 2020)
Blood being the chief circulatory medium in human body, participates in every functional activity by virtue of its circulation through every organ. Almost in all diseases the blood undergoes major changes in chemical and biochemical properties. The study of blood by spectroscopic technique can be used not only for understanding the biological nature of the disease, but also for the diagnosis of the prostate cancer .In the present work, Fourier Transform Infrared (FTIR-ATR) technique is employed to study the spectral differences between a healthy serum and that affected with prostate cancer .we found the absorbance of patients with prostate cancer larger than the absorbance of health men .We found that some functional groups were lost in the spectrum of patients, in addition to the occurrence of a shift in the spectrum of patients from the spectrum of healthy people, which can be used in the early diagnosis of diseases. In this study, P-values were lower than 0.05 (P< 0.05) for each ratio A1, A2, A3 showed 0.010,0.012,0.016 respectively, It was statistically significant, while the ratio A and A5 It was not statistically significant , Therefore, it is possible to take into consideration the ratio values of each A1, A2, A3 in the early diagnosis of prostate cancer, as well as in distinguishing between healthy and malignant tissues in the prostate gland in men.